Airport Infrastructure Development Strategy To Increase The Number Of Airlines At Tampa Padang Airport, West Sulawesi Province - Nofianti, Risma; Sainuddin, Sainuddin; Suryani, Herni; Ridhayani, Irma; Syahrullah, Syahrullah (Universitas Sulawesi Barat, 2026)
This study aims to formulate an effective airside infrastructure development strategy at Tampa Padang Airport (Class II Airport, Category 4C) to attract new airlines and support the economic potential of West Sulawesi. Using a qualitative descriptive method with SWOT analysis (IFAS and EFAS matrices) as the main strategic analysis tool, the results show that the airport is internally in a strong position (IFAS score: 3.68), supported by qualified human resources and adequate apron capacity. However, several critical weaknesses remain, namely the limited Taxiway Light System, the absence of a Precision Navigation System (ILS/PBN), and a PCN value that restricts larger or heavier aircraft. Externally, the airport is in a very favorable position (EFAS score: 3.91), driven by the potential recovery of the air transport market (LLAU) and strong tourism potential. The biggest threat is the difficulty of land acquisition for runway extension. The most effective development approach is an intensive strategy (SO strategy). Key recommendations include: (1) increasing the PCN and runway pavement strength to accommodate Code 4 aircraft (B737 series); (2) total rehabilitation of the Taxiway Light System and installation of ILS/PBN; and (3) acceleration of land acquisition to realize runway extension in accordance with the Master Plan.